2021
DOI: 10.1111/jvim.16003
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the intestinal mucosal proteome in cats with inflammatory bowel disease and alimentary small cell lymphoma

Abstract: Background: Current tests for diagnosis and differentiation of lymphoplasmacytic enteritis (LPE) and small cell lymphoma (SCL) in cats are expensive, invasive, and lack specificity. The identification of less invasive, more reliable biomarkers would facilitate diagnosis. Objectives: To characterize the mucosal proteome in endoscopically obtained, small intestinal tissue biopsy specimens. We hypothesized that differentially expressed proteins could be identified and serve as biomarker candidates for the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“… 22 However, western blot analysis did not confirm significant differential protein expression. 22 The utility of serum proteomics in diagnosis of CE in cats has not been explored.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“… 22 However, western blot analysis did not confirm significant differential protein expression. 22 The utility of serum proteomics in diagnosis of CE in cats has not been explored.…”
Section: Introductionmentioning
confidence: 95%
“…The discovery of new proteomic biomarkers is a multi‐phase process which involves screening for potential biomarkers using an untargeted approach with a small sample size at the discovery phase followed by verification of selected proteins using targeted approaches with a larger sample size at the validation phase 20,21 . A recent study investigated the intestinal mucosal proteome in cats with 9 proteins found to be differentially expressed between healthy cats and cats with IBD and LGAL 22 . However, western blot analysis did not confirm significant differential protein expression 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently applied in the field of veterinary gastroenterology through the study of the fecal proteome in healthy dogs and cats, and in dogs suffering from chronic enteropathies, as well as in cheetahs [ 8 , 9 , 10 , 11 , 12 ]. In one study in cats, the gastrointestinal (GI) mucosal proteome was also characterized in patients with inflammatory bowel disease, alimentary small cell lymphoma, and healthy controls [ 13 ]. Among the focal purposes of proteomics, there is the discovery of biomarkers to be applied for diagnostic/monitoring purposes, and more in general for a better understanding of the pathophysiology of determined conditions in specific biological environments.…”
Section: Introductionmentioning
confidence: 99%
“…This discipline is used to understand better the processes that take place in specific biological environments but also aims at the possible discovery of new biomarkers to differentiate a healthy status from a disease status and to monitor disease/treatment response [1]. This approach has recently been applied to fecal samples and intestinal biopsies in healthy and diseased Animals 2023, 13, 2343 2 of 15 animals to investigate and better understand the canine and feline gastrointestinal (GI) tract and related digestive disorders [2][3][4][5][6][7][8]. The study/discovery of new biomarkers in canine and feline GI disorders is indeed a topic of great interest [9].…”
Section: Introductionmentioning
confidence: 99%